Anticancer and Hepatoprotective Role of Selenium Nanoparticles against Liver Carcinogen Acrylamide Induced Toxicity: In vitro and in vivo Studies - Faridi, Uzma; Zidan, Nahla; Atteia, Hebbatallah; Al-Awthan, Yahya; Alalawy, Adel I; Akhtar, Md. Qussen; Sakran, Mohamed; Parveen, Humaira (Indian Journal of Pharmaceutical Education and Research, 2024)
Background and Objectives Selenium is considered one of the essential components of many enzymes, particularly the antioxidant enzymes such as thioredoxin reductase. Vegetables, among other food sources, are common sources of selenium. In the present study, the green synthesis of Selenium nanoparticles (SeNPs) from Ocimum basilicum’ aerial part was carried out, as were the anticancer and hepatoprotective roles of selenium nanoparticles against liver carcinogen acrylamide-induced toxicity. Materials and Methods The classification of SeNPs was done by different spectroscopic methods, including UV-spectroscopy, FT-IR, XRD, and HR-TEM. The synthesized SeNPs were tested for their anticancer properties using MTT assays (the normal human liver fibroblast cell line (WISH) and Human liver cancer (HepG2), respectively). Results The histopathological studies indicated that the liver acrylamide induced in mice showed necrosis and damage in liver cells, but the treatment of mice with SeNPs, reduced the effect of acrylamide significantly. Conclusion The results indicated the protective effect of SeNPs on acrylamide-induced cells both in vitro and in vivo.
Keywords: Selenium nanoparticles (SeNPs); Green synthesis; Acrylamide; Cytotoxic activity; Hepatoprotective; Anticancer